2015
DOI: 10.1103/physrevb.92.205109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stoichiometry and substitution in quasi-one-dimensional iron chalcogenideBaFe2S3

Abstract: The effects of off-stoichiometry and elemental substitution on electronic properties of iron-based ladder compound BaFe2S3 are investigated. Resistivity and magnetization are revealed to be quite sensitive to the stoichiometry of Fe atoms, and 10 % deficiency at Fe sites reduces the antiferromagnetic transition temperature by 40 K. The antiferromagnetic transition temperature decreases even faster and collapse to zero with hole doping through 10 % K substitution at Ba site, while the antiferromagnetic ordering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
46
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 34 publications
8
46
3
Order By: Relevance
“…(iii) The maximum value of T N at the pressure-induced QPT is also characteristic of Mott critical coupling under the influence of strong Hund's rule coupling [35,36]. (iv) An unknown transition at about 200 K [7,18] tends to decrease and merge with T N as pressure increases [7,20]. This transition is possibly related to orbital ordering and hints of the critical role of the orbitals in forming the magnetic ground state in BaFe 2 S 3 .…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…(iii) The maximum value of T N at the pressure-induced QPT is also characteristic of Mott critical coupling under the influence of strong Hund's rule coupling [35,36]. (iv) An unknown transition at about 200 K [7,18] tends to decrease and merge with T N as pressure increases [7,20]. This transition is possibly related to orbital ordering and hints of the critical role of the orbitals in forming the magnetic ground state in BaFe 2 S 3 .…”
mentioning
confidence: 93%
“…3(f)]. The order parameter on cooling shows no hysteresis, suggesting the glassy behavior in Ba 1−x Cs x Fe 2 Se 3 [17] and Ba 1−x K x Fe 2 S 3 [18] is likely caused by the change of carrier concentrations. Fig.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Yamauchi et al conducted dc resistivity measurements and observed a maximum in T N at ∼ 3 GPa followed by a monotonic reduction with increasing pressure [6]. Reasons for the discrepancy could be anisotropies in the resistivity or slightly different stochiometries [25]. The increase of T N between 0 and 7.5 GPa can be explained by an increase of the exchange interaction [14].…”
mentioning
confidence: 99%
“…In both systems, the FeX 4 edge-sharing tetrahedra create well-separated iron ladders [11], distinct from the planar square lattice of other FeSCs. These compounds therefore represent an important new family of materials that has attracted significant theoretical and experimental attention in the quest to understand iron-based superconductivity [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. BaFe 2 S 3 belongs to the orthorhombic space group Cmcm and orders antiferromagnetically below ∼100-120 K in a stripe-type spin configuration [8].…”
mentioning
confidence: 99%